Preliminary pilot fMRI study of neuropostural optimization with a noninvasive asymmetric radioelectric brain stimulation protocol in functional dysmetria - Mura M (Dove Medical Press, 2012)
Marco Mura1, Alessandro Castagna2, Vania Fontani2, Salvatore Rinaldi21Institute of Radiology, University of Cagliari, 2Rinaldi Fontani Institute – Department of Neuro Psycho Physical Optimization, Florence, ItalyPurpose: This study assessed changes in functional dysmetria (FD) and in brain activation observable by functional magnetic resonance imaging (fMRI) during a leg flexion-extension motor task following brain stimulation with a single radioelectric asymmetric conveyer (REAC) pulse, according to the precisely defined neuropostural optimization (NPO) protocol.Population and methods: Ten healthy volunteers were assessed using fMRI conducted during a simple motor task before and immediately after delivery of a single REAC-NPO pulse. The motor task consisted of a flexion-extension movement of the legs with the knees bent. FD signs and brain activation patterns were compared before and after REAC-NPO.Results: A single 250-millisecond REAC-NPO treatment alleviated FD, as evidenced by patellar asymmetry during a sit-up motion, and modulated activity patterns in the brain, particularly in the cerebellum, during the performance of the motor task.Conclusion: Activity in brain areas involved in motor control and coordination, including the cerebellum, is altered by administration of a REAC-NPO treatment and this effect is accompanied by an alleviation of FD.Keywords: motor behavior, motor control, cerebellum, dysmetria, functional dysmetria, fluctuating asymmetry